Aerodynamic characteristics of a super high-speed elevator with different toe guards. Issue 233 (February 2023) - Zhang, Jun; Jin, Shenxin; Qin, Lei; Ma, Jiancheng; Zhang, Hong; Xu, Lei; Jiang, Jiahui; Jia, Guangchen; Hu, Yuan
Abstract: To reduce the drag and noise of a super high-speed elevator, a certain type of elevator in operation with different toe guards was taken as the subject to conduct research on its aerodynamic characteristics. In this study, a numerical simulation model was established and used to carry out experiments, and by comparing the theoretical and experimental results, the validity of the method was verified. First, a 3-D unsteady numerical model was established based on improved unstructured dynamic grid method, and the Reynolds average N–S equation was solved by SIMPLEC algorithm. Then, the whole running process of the elevator was simulated, including the velocity distribution, vorticity strength, and pressure gradient in the flow field were analyzed. Finally, the aerodynamic characteristics of the elevator with different vertical heights and four structure layouts of the toe guard were analyzed. The results show that the drag reduction effect is quite apparent when toe guards are installed at the car's top and bottom. In addition, it was found that decreasing the vertical height of the toe guard is conducive to reducing resistance and saving space in the elevator car. The inclusive analysis not only explores the aerodynamic characteristics of super high-speed elevators but also recommends structural optimization design. Highlights: A dynamic grid numerical method was proposed to simulate the flow field near the car of a high-speed elevator. The theoretical model of induced airflow movement was established in high-speed elevator. The aerodynamic characteristics of high-speed elevators with different toe guards were obtained.